Writing the Hyper-Disaster: Embodied and Engendered Narrative after Nuclear Disaster. - JONES, EMILY (Comparatist, 2017)
The article explores the difficulty of decommissioning and containing the Fukushima Daiichi nuclear power plant disaster in Japan on March 11, 2011. It mentions that the number of missing persons adds uncertainty element on the ultimate damage that the Tohoku earthquake caused which is reminiscent of the speculation about the effects of Chernobyl, coupled with the spread of Fukushima radiation and the risks associated with its cleanup.